KESULITAN MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU DALAM MEMAHAMI TEKS DOKKAI TINGKAT DASAR - Lestari, Weni Puji; Hadriana, Hadriana; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the difficulties of students in understanding basic level dokkai texts. The purpose of this study was to determine the difficulties experienced by students in understanding basic level dokkai texts. The method used in this research is quantitative with a descriptive approach. The data was obtained by distributing questionnaires to 28 students of the 2020 class of Japanese language education FKIP Riau University. The results of this study indicate that students have difficulty in understanding basic level dokkai texts. In general, students experience difficulties in all indicators, namely grammatical competence, sociolinguistic competence, discourse competence and strategic competence. In particular, students have difficulty in grammatical and discourse competence. Grammatical and discourse competencies have an important role in understanding dokkai texts. In grammatical competence there are letters, vocabulary and sentence patterns that must be mastered, while discourse competence is the relationship between one sentence and another.Key Words: Difficulty, basic level dokkai text, Japanese language education.